2021
DOI: 10.1080/00207411.2021.1984127
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 lockdown and mental health: Exploring triggers of mental health distress among women in the Copperbelt province, Zambia

Abstract: More than 60,000 deaths from COVID-19 had been confirmed as of the 1st of August 2020. Concerns about physical and psychological wellbeing had increased across the world with women disproportionately being affected. This research was set to explore the triggers of mental health distress among women during COVID-19 lockdown. The research study utilized a qualitative descriptive approach. Forty (N ¼ 40) women were recruited to take part in the research study. A one to one semi structured interview schedule was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In our study, we found that younger mothers (less than 30 years old) and women with less than three children under their care were most strongly affected by deteriorating mental health scores during the COVID-19 pandemic. Qualitative research from Zimbabwe, Malawi and Zambia and quantitative research from South Africa have highlighted food insecurity, childcare responsibilities, increases in domestic violence events, and pre-existing health conditions as main factors for mental health distress during the pandemic in this setting [22,[42][43][44]; it is possible that younger women as well as less educated women were disproportionally affected by these factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found that younger mothers (less than 30 years old) and women with less than three children under their care were most strongly affected by deteriorating mental health scores during the COVID-19 pandemic. Qualitative research from Zimbabwe, Malawi and Zambia and quantitative research from South Africa have highlighted food insecurity, childcare responsibilities, increases in domestic violence events, and pre-existing health conditions as main factors for mental health distress during the pandemic in this setting [22,[42][43][44]; it is possible that younger women as well as less educated women were disproportionally affected by these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies evaluated women's mental health during the COVID-19 pandemic in Zambia. One showed high levels (above 40%) of stress and anxiety among health professionals [21] and a qualitative study exposed widespread perceptions of reduced access to healthcare due to lack of transportation during lockdowns and increased stress among women related to increased domestic violence events, loss of employment, childcare demands, and family isolation [22]. However, there is currently no evidence on changes in mental health distress among women in the country from before to during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The centralized arc of dealing with mental health patients, also affects community sensitization and home-based care treatments initiatives, in some cases, leads to suicides. Common mental disorders leading to suicides include acute psychotic episodes, schizophrenia, affective disorders, alcohol related problems and organic brain syndromes (Nyashanu, Karonga, North, Mguni, Nyashanu 2021. During his State of Address to the Nation (SONA) in 2021, Zambia's Republican President, Edgar Chagwa Lungu revealed that the prevalence rate of suicides stood at 17.5 per 100,000 males against 6.2 among females.…”
Section: Inadequate Infrastructure For Mental Patients: the Debate Ar...mentioning
confidence: 99%
“…Further, the debate on collateral damage has been brought to the fore by the current impact of COVID-19 on numerous spheres of Zambian society. In recent times, Nyashanu et al (2021) conducted a study on the triggers of mental health distress among women during COVID-19 lockdown in the Copperbelt province of Zambia. The study found that, there is cause -effect relationship between long periods of staying indoors and mental health distress among the research participants.…”
Section: Inadequate Infrastructure For Mental Patients: the Debate Ar...mentioning
confidence: 99%
“…At the beginning of the pandemic there was no vaccine and effective treatment for COVID-19 infection. Therefore, for controlling the rapid transmission of the disease, many non-clinical interventions were suggested by the World Health Organization (WHO) such as social distancing, cleanliness, regular hand washing, use of face masks in public, lock-down, restriction on travel, closure of local and international flights, bans on large gatherings, social distancing, shutdown of educational institutions, stay-at-home orders, and even curfews [7][8][9][10][11]. Simultaneously, the overburden of information, rumors, and misinformation further irritate the general population's mental health status [12].…”
Section: Introductionmentioning
confidence: 99%